PENGARUH MODAL KERJA TERHADAP PROFITABILITAS DI RUMAH SAKIT HERNA MEDAN - MONTARIS SILAEN; LASMAN EDDY BACHTIAR; RIANTO . (LP2MTBM MAKARIOZ, 2022)
With good working capital management, it automatically affects the level of profitability of the company. RSU Herna Medan isa company engaged in health. Given the importance of working capital for the company, Herna Medan General Hospitalrequires the effective, efficient and productive use of working capital to increase the company's profits. The formulation of theproblem in this study is